(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Globalization is a process of interaction and integration among the people, companies, andgovernments of different nations whereas Liberalisation refers to laws or rules being liberalized or relaxed,by government. This paper attempts to examine the impact of globalization and liberalization ongovernment . Changes that are sweeping rapidly across the business world have forced businesses andnations to adapt by striving to change old economic behaviour’s and traditional practices. Issues thatarising out of globalization have rapidly altered the nature and scope of public administration. No longerconfined to the analysis of the structure of the administration. Many functions of public sectors arebeing abstract and the interaction and copying of the public and private sectors has been increasing,which has been proving beneficial to the public sector to make it efficient, accountable, transparent, andcompetitive. This paper also examines the negative impacts of globalization on Indian administration likeFlexibility in policies, increase in production, lessen the burden of work of administration with lesscontrol on economic and commercial activities.